Microbiological processing of sewage sludge into organo-mineral fertilizer on the example of Astanaand Aktau - Aigerim Issabekova; Zhanat Idrisheva; Zina Tungushbayeva; Assyl Shakhanova; Manira Zhamanbayeva; Arailym Amantayeva; Elnara Kuandykova; Indira Raiymbekova (Caspian Journal of Environmental Sciences)
Sludge from wastewater treatment is a complex and challenging by-product of water treatment processes. Despite the technical, environmental, and health challenges, this material can be valuable in agriculture, industry, and energy production. Sewage sludge with organic matter is considered a macro source of micro and macro elements. New technologies and compliance with health and environmental standards are essential for better sludge management. Considering the need for sustainable resources and environmental protection, the future of sludge use looks promising and can help reduce environmental impacts and increase resource efficiency. The introduction of organic matter into the soil by affecting different physical, chemical, nutritional, and biological characteristics of the soil can improve or increase the growth of plants. As a result of microbial processes and under the influence of intracellular and extracellular enzymes, the ground is provided for plant growth by changing the form of elements from organic to inorganic form. This study investigates the effect of different levels and frequencies of fertilization with sewage sludge on soil activity and quality. For this purpose, wastewater and soil analyses were used, and wastewater treatment was evaluated using two liquid sludge methods for organic fertilizer and bulking materials for mineral fertilizer. The results showed that by changing the volume of treated materials and the amount of wastewater added to the soil, the characteristics of the soil change over a 2-year period. In general, the application of sewage sludge increased the organic carbon and total soil nitrogen and enzyme activities in the soils treated with sewage sludge.